Prediction Of PM10 Using Multiple Linear Regression And Boosted Regression Trees - Hamid, Nur Haziqah Mohd (Universiti Sains Malaysia, 2017)
Particulate matter with an aerodynamic diameter less than 10μm (PM10) is one of the pollutants that can adversely affect human health. The aims of this study is to predict particulate matter concentration for the next day (PM10D1) by using Multiple Linear Regression (MLR) and Boosted Regression Trees (BRT) models. The daily mean data used from 2013 until 2015 is divided into training data (70%) and validation data (30%). The parameters that influence PM10 concentration for the next day are particulate matter (PM10D0), wind speed (WS), temperature (T), relative humidity (RH), sulphur dioxide (SO2), nitrogen dioxide (NO2), ozone (O3) and carbon monoxide (CO). Daily mean data were selected at four monitoring stations which are Jerantut (background station), Nilai (industrial area), Seberang Jaya (sub-urban area) and Shah Alam (urban area). The results obtained shows that Nilai station recorded the highest mean value of PM10 concentration compared to other stations. The main contributions of air pollution at Nilai station are particulate matter (PM10D0), carbon monoxide, nitrogen dioxide and ozone. The result shows that Multiple Linear Regression models (MLR) is the better model to predict the next day of PM10 concentration compared to Boosted Regression Trees (BRT).